Identifying the prevalence of genito-anal injuries amongst clients attending St Mary's Sexual Assault Referral Centre following an allegation of anal penetration. (August 2022) - Buswell, Harriet; Majeed-Ariss, Rabiya; Rajai, Azita; White, Cath; Mills, Helen
Abstract: Background: There is a lack of clarity around the prevalence of anal injuries sustained following anal penetration. The aim of this study was to identify the prevalence of injury amongst clients attending Saint Mary's Sexual Assault Referral Centre (SARC), Manchester, UK following anal penetration and identify predisposing or protective factors such as age, sex and pubertal status. This should facilitate an evidence-based approach to providing evidence statements in court for allegations of anal penetration. Method: This was an observational retrospective study analysing the forensic medical examination (FME) case notes of 239 clients between January 2015 and December 2016. Subjects were excluded if the nature of alleged assault was unclear. Data was extracted from the FME case notes on to a data collection proforma and statistical analysis undertaken. Results: Of the 239 subject, 156 [65.3%] were female and 83 [34.7%] male. Subjects were predominantly post-pubertal, 185 [79.4%]. The alleged assaults were categorised in to penile anal, digital anal and object anal; penile anal assault was the most common type, 177 [75.97%]. No association was found between type of assault and presence of anal injury. Anal injuries did not occur more frequently in one sex than another [21.15% female, 21.69% male]. Logistic regression indicated pre-pubertal children were less likely to have injury [(odds ratio = 0.34, 95% CI (0.078, 0.70), p = 0.016)], although this was not significant when adjusted for time since assault. Most pre-pubertal children presented more than 72 h after alleged assault, [68.2% female, 73.1% male] The presence of anal injury was significantly associated with time since assault across all subjects, with those examined after 72 h less likely to have injury [p = 0.0016]. A greater proportion of single suspect assaults [22.8%] resulted in anal injury than multiple suspect assaults [13.9%]. Whilst there was alcohol consumption in most alleged assaults against post-pubertal subjects [56.1% female, 50.9% male], there was no statistically significant data to associate alcohol consumption with anal injury. And, the same was true of drug consumption. Among post-pubertal females 96.21% of assaults involved threats or violence, comparable with 71.70% amongst post-pubertal males. The data did not suggest threats and violence increase the rate of anal injury. Conclusion: The study identifies a statistically significant relationship between time since assault and prevalence of anal injury. Further, a relationship between pubertal status and prevalence of anal injury was found. The low prevalence of anal injury amongst pre-pubertal children suggests that absence of injury at the time of examination, following allegation of anal assault, is a common finding. Importantly, whilst not demonstrating statistical significance, it should be noted that the majority of assaults reported in the study did not result in anal injury. The study provides contemporary evidence in the field of forensic medicine which can be used in court proceedings in allegations of anal assault. Highlights: Most alleged assaults did not result in anal injury. Drug and alcohol consumption was not associated with anal injury. More than 2/3 pre-pubertal children presented 72 h after assault.